Strategi Pengembangan Manajemen Peserta Didik Dalam Meningkatkan Mutu Pendidikan Di MTs Dar El Fathrizk Pekanbaru - Vebri Pradinata Putra; Parisyi Algusyair; Nurhayuni Nurhayuni; Muslim Afandi (Al-Amin: Jurnal Ilmu Pendidikan dan Sosial Humaniora, 2023)
Education is a very important need for every human being. The existence of an educational institution is no exception for students who will fill the institution with their various potentials, talents and interests. Students are raw materials that must be processed into intellectual beings who are able to compete in today's era, so that the purpose of education will be achieved by forming the character of students who are good, have good morals so that they can be accepted in society. In an educational institution, of course they have their own ways and strategies for improving school quality. This article discusses how schools improve the quality of education through student management by training students in various activity agendas, developing students' interests and talents and how strategies are in accepting new students